EFFECT OF VIRGIN COCONUT OIL SUPPLEMENTATION ON AFB SPUTUM CONVERSION RATE, SOD, AND BMI LEVELS IN PULMONARY TUBERCULOSIS PATIENTS - Muhammad Ajib Nuzula; Mohamad Isa; Juhairina; Haryati; Isa Ansori; Erna Kusumawardhani (Majalah Biomorfologi, 2024)
Highlights 1. VCO can accelerate AFB sputum conversion in tuberculosis infection. 2. VCO can decrease SOD levels as a marker of inflammation.   Abstract Background: Pulmonary tuberculosis has the potential to raise illness and death rates on a global scale significantly. A low sputum conversion rate for acid-fast bacilli (AFB) and malnutrition are indicators of failure in pulmonary TB treatment. Virgin coconut oil (VCO) contains lauric acid and has antibacterial, antioxidant, and anti-inflammatory effects. Objective: This study aimed to examine the effect of VCO supplementation on sputum AFB conversion rates, superoxide dismutase (SOD) levels, and body mass index (BMI) status of pulmonary TB patients. Material and Methods: This study was an analytic experimental study measuring BMI levels and SOD levels at the Pekauman Community Health Center, Sultan Suriansyah Hospital, and Ulin Hospital, Banjarmasin, Indonesia, between July and September 2023. This study, 40 samples were separated into two groups: the treatment group, which received first-line antithyroid drugs (ATD) with VCO, and the control group, which received first-line ATD and a placebo. Results: Based on the proportion, there was an improvement in the acceleration of BTA sputum conversion, and from the mean BMI and the median value of both groups, there was a decrease in SOD levels after VCO administration. No statistically significant association was found between VCO administration and accelerating the AFB sputum conversion and BMI at the end of the fourth and eighth weeks (p>0.05). Additionally, there was no relationship considered between VCO administration and reducing SOD levels before and after treatment (p>0.05). Conclusion: VCO administration had no relationship with the level of AFB sputum conversion, reduction in SOD levels, and BMI status in pulmonary TB patients.